The Plans for the Abolition of the Zaporozhian Host and their Implementation (1740s–1770s): Cossack Ambitions vs Imperial Interests - Milchev, Vladimir; Sen', Dmitry (Quaestio Rossica, 2018)
Referring to materials from the federal and state archives of Russia and Ukraine, the authors analyse the preparation and implementation of the abolition of the Zaporozhian Cossack Host, carried out by the government of Empress Catherine II. Many of the sources have never been studied previously. The authors aim to reveal the causes and reasons for the abolition of the Sich, and the timeframe of the process. The authors consider the plans and projects for the abolition of the Sich from different periods and proposed by different representatives of the imperial authorities. The authors prove that the abolition of the Zaporozhian Sich was not a one-time military operation that took place on 4 June 1775. They study the means by which the Russian authorities tried to solve the Zaporozhian problem during the third quarter of the 18th century, reflected in the projects drawn up by M. I. Leontyev, P. A. Rumyantsev, and K. von Stoffeln. They examine the socio-economic, demographical, political, and other aspects of the domestic and foreign policy of the Russian Empire, which influenced the social evolution of the Zaporozhian Cossacks Host and led to its confrontation with the government. Additionally, the article considers the reaction of the Cossack community to the abolition of the Sich.